2022
DOI: 10.1007/s10346-022-01877-9
|View full text |Cite
|
Sign up to set email alerts
|

UAV applications to assess short-term dynamics of slow-moving landslides under dense forest cover

Abstract: The paper presents a methodology to rapidly assess and map the landslide kinematics in areas with dense vegetation cover. The method uses aerial imagery collected with UAVs (Unmanned Aerial Vehicles) and their derived products obtained from the structure from motion technique. The landslide analysed in the current paper occurred in the spring of 2021 and is located in Livadea village from Curvature Subcarpathians, Romania. This landslide affected the houses in the vicinity, and people were relocated because of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 56 publications
0
12
1
Order By: Relevance
“…Detailed spatial topography will be derived, and key surface features of the conditions before and after the landslide will be analyzed. The previous study has demonstrated the advantage of using UAV for landslide investigations [21][22][23]. There is proof that landslide movements can be mapped with centimeter accuracy using time-series UAV images [24].…”
Section: Methodsmentioning
confidence: 81%
“…Detailed spatial topography will be derived, and key surface features of the conditions before and after the landslide will be analyzed. The previous study has demonstrated the advantage of using UAV for landslide investigations [21][22][23]. There is proof that landslide movements can be mapped with centimeter accuracy using time-series UAV images [24].…”
Section: Methodsmentioning
confidence: 81%
“…[75][76][77] For inaccessible field areas, the DJI Phantom 4 RTK (DJI-P4RTK) UAV can be used to obtain ultra-high spatial resolution images, and the entire process is not restricted by geographical conditions. 78,79 In addition, satellite data of the study area in the same temporal phase, such as Aster and WorldView-3, can be acquired. 65,[80][81][82] These images are used to obtain the exposed lithology of the study area and further validate the classification results.…”
Section: Discussionmentioning
confidence: 99%
“…High nega Finally, the volume trapped into terraces was estimated by computing the difference between the actual surface and the interpolated one. The computation of the DoD (DEM of differences) is widely used to characterize the Earth's changing surface [44][45][46]. The calculation was repeated for every single identified slope.…”
Section: Terrace Detectionmentioning
confidence: 99%